Lived Experiences of Farmers in Catanduanes after Super Typhoon Pepito (Man-yi): A Phenomenological Study - Rubio-Valenzuela, Vivienne May (JPAIR Multidisciplinary Research, 2026)
This study explored the lived experiences of farmers in Catanduanes, Philippines, following the devastation brought by Super Typhoon Pepito (Man-yi) in 2024. Employing a qualitative phenomenological research design, the study utilized in-depth, semi-structured interviews to gather narratives from purposively selected farmers-participants. The study involved 20 agricultural farmers, selected based on Subedi’s (2021) recommendation of number of participants for narrative inquiry and guided by the principle of data saturation. Data were analyzed using Colaizzi’s method which involved extracting significant statements, formulating meanings, and clustering them into emergent themes. The results revealed five major themes: fear and vulnerability, economic disruption and livelihood fragility, coping and recovery through self-reliance and community support, support system gaps, and spiritual and emotional resilience. The study concludes that while farmers exhibit strong internal and communal resilience, sustainable recovery remains constrained by systemic vulnerabilities and post-disaster livelihood support. It is recommended that policymakers and development institutions implement inclusive, community-centered disaster risk programs designed for long-term livelihood rehabilitation.